TRIP-based transport travel demand model for intelligent transport system measure evaluation based on micro simulation. (2017) - Zenina, Nadezhda; Merkuryev, Yuri; Romanovs, Andrejs
Nowadays, the systems developed to integrate real physical processes and virtual computational processes - the cyber-physical systems, are used in multiple areas such as medicine, traffic management, automotive engineering, industrial robots, nanotechnology and biological systems technology. The current paper provides an overview of CPS, their application in different fields of modern business, with main video recording accent to intelligent transport system. Various transport travel demand models are considered: trip-based, tour-based and activity-based. Strengths and weaknesses of each transport travel demand model are described. ITS strategies and its evaluation measures are considered for transport intelligent transport system effective management. An example of transport management solutions realisation process based on transport microscopic modelling is presented. The example is illustrated for one of the Latvian cities - Adazi, where it was necessary to improve accessibility level for local drivers for three to five-year periods in future by evaluating different ITS measures combined with traffic organisation scheme changes.